ANALISIS KEMACETAN DAN GANGGUAN LALU LINTAS DI KOTA TERNATE TENGAH DITINJAU DARI ASPEK DAN PERILAKU DAN BUDAYA MASYARAKAT - Sultan, Mufti Amir; Susanto, Edi; Samad, Sudarman; Gaus, Abdul (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2024)
One of the significant impacts of population growth is an increase in the number of movements. In a social context, an efficient transportation system can improve the quality of life, enable better accessibility, and form connectivity between individuals and communities. This growth must of course be balanced with the development of adequate road infrastructure to provide a sense of security and comfort for road users. However, there are other aspects that also influence the spatial planning and use of roads in the city of Ternate, namely the behavior and social habits of the community which have become part of culture and daily life. The practice of using public roads as a place to hold various celebrations or ceremonial events is part of the social interactions and habits of local communities. Based on research results, the culture of closing roads for celebration events, which results in traffic disruption, comfort and traffic jams, is a phenomenon that is truly natural and occurs in the social life of the people of Ternate City today. The expected solution is regional government firmness in implementing regional regulations regarding road closures by the community, in this case included in regional regulations related to public order and the provision of facilities for social interaction such as the provision of village halls for event activities and the provision of multi-purpose building facilities which also need to be carried out by local government. With this effort and attention, it is hoped that it can change the community's mindset in using roads as activities for celebrations and other events, but without eliminating the traditions and culture that are embedded in the social life of the people of Ternate City.